Kepok Tarik’s / Amriena Roshyada Zamlan - Amriena Roshyada, Zamlan (2020)
Kepok Tarik’s business is offers keropok lekor in corn dog version with the concept of half-local and western snack food. Kepok Tarik’s produce the product which are Kepok Tarik Original and Kepok Tarik Crunchy. Kepok Tarik Original served with the originality taste of keropok lekor combined with the cheesy of mozarella with the sauce. Kepok Tarik Crunchy is addition recipe which is topping with the crunch of cornflake cereal in order to variety the taste. Kepok Tarik’s is owned by Amriena Roshyada Zamlan. Amriena has extensive experience in serving and producing food for 1 year being a part-timer at one of successful restaurant in Terengganu. Kepok Tarik’s produce trendy snack for those that loves keropok lekor in having their chilling time. For those that did not like keropok lekor, this company guarantee that once people taste this Kepok Tarik’s, they will love it. So, Kepok Tarik’s targetting family, teenager and tourists. The market reasearch has resulting eight out of 10 people in Terengganu would love this product since this product offers tasty and affordable snack. While there are currently three business offering corndog snack in Kuala Nerus, with same taste of corndog, Kepok Tarik’s produce an innovation product that shows diferrentation from the competitors’ product. This is the advantage for Kepok Tarik’s to gain the customer target. This product also have a different taste compared with competitors’ product. Based on the size of market and defined market area, sales projections for first year are RM87,840. The profit that gain already increasely secured in the future for the next two years if the size of target market maintained and increase. On start up, Kepok Tarik’s will have two trained staff to provide food service and expect to hire three more staff once financing is secured. Kepok Tarik’s plan to aggresively build the customer base through website, social media and direct mail advertising.